Design and implementation methodology for rapid control prototyping of closed loop speed control for BLDC motor - Devendra Potnuru; Alice Mary K.; Saibabu Ch. (Journal of Electrical Systems and Information Technology, 2018)
This paper deals with rapid control prototyping implementation of closed loop speed control for a Brushless dc (BLDC) motor drive using dSPACE DS1103 controller board. Generally control algorithms which are developed for the motor drive might show good simulation results during steady state and transient conditions; however real-time performance of the drive greatly depends on execution of real time control software, speed and position measurements and data acquisition. The real challenge of hardware implementation lies in selecting appropriate hardware equipment and perfect configuration of the equipment with controller board. The dSPACE DS1103 controller board is suitable for high performance electric motor control as it has flexibility of converting the MATLAB/Simulink blocks into DSP enabled embedded code. In this paper a detailed procedure to effectively control the BLDC motor drive in real-time is presented. Keywords: BLDC motor, Rapid control prototyping, dSPACE, DS1103